Event-based feedforward control of linear systems with input time-delay - Rodríguez, Carlos; Aranda-Escolástico, Ernesto; Guinaldo, Maria; Guzmán, José Luis; Dormido, Sebastián (Zielona Góra: Uniwersytet Zielonogórski)
This paper proposes a new method for the analysis of continuous and periodic event-based state-feedback plus static feedforward controllers that regulate linear time invariant systems with time delays. Measurable disturbances are used in both the control law and triggering condition to provide better disturbance attenuation. Asymptotic stability and L2-gain disturbance rejection problems are addressed by means of Lyapunov - Krasovskii functionals, leading to performance conditions that are expressed in terms of linear matrix inequalities. The proposed controller offers better disturbance rejection and a reduction in the number of transmissions with respect to other robust event-triggered controllers in the literature.
Keywords: time delay systems; linear systems; process control; control system design